A jurisprudência uniforme como elemento estruturante do sistema jurídico brasileiro - Cimardi, Cláudia Aparecida (2014)
This thesis aims to analyze the current role of jurisprudence in the face of Brazilian legal system. First, the historical aspects that led to the evolution of the concept of legal system were presented. From these considerations, the following approaches were conducted: (i) historical delineation of the development of law enforcement, especially in the Civil Law legal system, showing how mass society demanded that the Brazilian legislator implanted new trial procedural techniques; (ii) presentation of the concepts of jurisprudence and judicial precedents to the Brazilian legal system; (iii) demonstration of need for the jurisprudence to be dedicated to standardization, function to be exercised by superior courts (Supreme Justice Court and Supreme Federal Court; (iv) demonstration that the performance of this function results a paradigm for future trials and, therefore, comply with the ideals of stability and predictability of the legal system; (v) exposure that uniform jurisprudence of higher courts can and must undergo changes, being inadmissible sudden and unjustified changes; (vi) demonstration of the importance of judicial precedents in the Brazilian legal system, as conductors of uniform jurisprudence; (vii) exposure of standardization techniques of jurisprudence governed by civil process, and (viii) new discipline of the subject, presented in the Draft ot Civil Process Law. As a result of the research, it was found that uniform jurisprudence of higher courts integrates the meaning of rules, reason why it is the structuring element of the legal system, hence it should be observed in future trials, throughout society and the Administration. We sought, therefore, to develop a methodical study, based on extensive local and foreign literature, which intended to establish a current legal framework of the uniform jurisprudence of higher courts and techniques for jurisprudence standardization